Modeling and simulation of distillation column - Ann, Ivy Wong Fui (2014)
This paper presents modeling and simulation studies of distillation column. This study is to stimulate sieve tray distillation (rate based model) and specifically for multiple columns process by using Aspen Hysys. The economic importance of distillation separations has been a driving force for the research in synthesis procedures for more than 30 years. Distillation accounts for almost 90% of the separation systems used in chemical process industries. The best way to reduce operating costs of existing units is to improve their efficiency and operation via process optimization and control. Simulation generates one or more trajectories (possible behaviors from the high-level model), and collects statistics from these trajectories to estimate the desired performance or dependability measures. Modeling and simulation of distillation column might already be very familiar but modeling and simulation of multicomponent distillation in multiple columns still yet being commercially introduced to the industries. In this project, the well known kind of multi components (n-butane, n-pentane and benzene) is chosen as the example to run this simulation by using multiple distillation columns. By inserting the details and specifications in Aspen Hysys, multicomponents distillation process is stimulated under steady state condition. From the result gained, calculations such as compositions, temperature, mass balance and energy balance can be done step by step. The composition, k values, temperature and flowrate will be further explained in discussion. Other than that, the limitations of steady state techniques are discussed, and the need for rigorous dynamic simulation for final selection of a workable and robust strategy is illustrated